2016
DOI: 10.1556/1646.8.2016.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after tonsillectomy versus azithromycin

Abstract: BackgroundRecurrent tonsillitis is a common disease with marked evidence of affecting children quality of life (QOL) such as their progression in school and increased burden to extended families. The aim of this study was to compare the QOL outcomes after conventional dissection tonsillectomy versus azithromycin treatment in controlling recurrent tonsillitis.MethodsA double-blind, randomized clinical trial was carried out in 184 children with recurrent tonsillitis randomly divided into two groups: Group A was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…An improvement in the quality-of-life after tonsillectomy has been reported in subjects undergoing repeated cycles of antibiotic therapy, but no randomized controlled trials evaluating the effect of tonsillectomy on the general well-being, development, and behavior of the child are available. These measures, however, represent important treatment outcomes to be inserted in future clinical research 4,5…”
Section: Introductionmentioning
confidence: 99%
“…An improvement in the quality-of-life after tonsillectomy has been reported in subjects undergoing repeated cycles of antibiotic therapy, but no randomized controlled trials evaluating the effect of tonsillectomy on the general well-being, development, and behavior of the child are available. These measures, however, represent important treatment outcomes to be inserted in future clinical research 4,5…”
Section: Introductionmentioning
confidence: 99%
“…Tonsillectomy morbidity has high impact on the QOL of patients such as socioeconomic factors and increased burden to parents from the suffering of the child. 18 Tonsillectomy should not be the only solution as there is a possibility of immunological deficit as the function of tonsils in the immune system is not completely clear as an important constituent of the upper respiratory tract defense system. 19 On the other hand, patients who undergone tonsillectomy are at high risk of developing bronchial asthma 20 and Crohn's disease 21 .…”
Section: In Groupmentioning
confidence: 99%
“…Patients received AZT alone had significant less tonsillitis attacks and less severe symptoms than patients who didn't receive any prophylaxis during the same period of the study. El Hennawi et al 18 in their study concluded that AZT is effective in prophylaxis against recurrent tonsillitis with a great benefit for better QOL compared to patients who had tonsillectomy, however; they used the prophylactic regimen of rheumatic fever prevention (once weekly AZT) 23 and they didn't include a control group in their study. Casey and Pichichero 24 reported that AZT treatment for GABHS tonsillopharyngitis in children and adults is more effective than other treatment regimens in providing clinical cure of tonsillopharyngitis.…”
Section: Patientsmentioning
confidence: 99%
“…The lifetime prevalence of common RT is 7-11% [9]. Only a few studies have addressed whether recurrent tonsillopharyngitis affects QOL in adults [1,5,6,10,11], although this has been well-studied in children [6,7,[12][13][14][15][16][17][18][19][20][21][22][23][24]. In 2012, Skevas et al introduced the Tonsillectomy Outcome Inventory 14 , which was the first worldwide-validated instrument to measure disease-specific QOL in adults with RT [25].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that tonsillectomy is associated with improved health-related quality of life (HR-QOL) [ 1 , 2 , 4 , 5 ], reduced medication consumption, less time off work, and fewer visits to the physician [ 6 ]. In another study, 75% of tonsillectomies for RT resulted in postoperative pharyngitis and upper respiratory tract infections [ 7 ].…”
Section: Introductionmentioning
confidence: 99%